Global methane pledge: An important climate action pathway for Tajikistan - Srivastava, Nandita; Babu, Suresh Chandra (Climate Links, 2024)
Methane is a potent greenhouse gas that is responsible for approximately 30 percent of the rise in global temperatures since the Industrial Revolution. Its high warming power sets the pace for warming in the near term.